Flexible Working of Place dan Stres Kerja terhadap Kinerja Karyawan dengan Perspektif Self Determination Theory: Studi Kasus pada Perusahaan Sewa Alat Berat di Kota Bandung - Ganjar Garibaldi; Neneng Hayati (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the effect of the variables: Flexible Working; Job Stress; on Employee performance, with the perspective of Self Determination Theory. Method: The research method used is causal associative using questionnaires and survey research methods which are part of a quantitative study with a sample of 60 respondents. The analysis in this study uses descriptive statistics, validity test, reliability test, classical assumption test, multiple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing. Results: Write only the results of research. The results showed that flexible working of place is in the medium category and work stress is in the high category, and employee performance is in the low category. Limitations: The limitations of this study are the lack of influence of exogenous variables that are not dominant enough in predicting employee performance with flexible work arrangements that have been carried out, and for further research it is necessary to add relevant exogenous and intervening variables such as: leadership, and employee involvement as a human factor from a different perspective. Wider. Contribution: The contribution of this research can be useful for practitioners in the world of work so that they can add to the basis for making decisions in work practice.